2016
DOI: 10.1159/000443212
|View full text |Cite
|
Sign up to set email alerts
|

Functional Results of Laparoscopic Pyeloplasty in Children: Single Institute Experience in Long Term

Abstract: Objective: The aim of this study was to evaluate the long-term functional outcomes of laparoscopic pyeloplasty (LP) in children for consecutive cases of single institute. Materials and Methods: Our laparoscopy database was investigated for children in terms of LP between June 2008 and April 2015. All the patients had ureteropelvic junction obstruction (UPJO) and LP was performed. Demographic data including age, gender, side of UPJO, operation time, estimated blood loss (EBL), hospital stay and complications ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Although most series report longer operative time in LP, (mean 155-240min) (3,8,11,16) we had spent a mean of 107min., which may be near the open procedures time. Previous adult experience, same team, routine and focusing on simplifying every step certainly play a role in the operative time.…”
Section: Discussionmentioning
confidence: 82%
See 4 more Smart Citations
“…Although most series report longer operative time in LP, (mean 155-240min) (3,8,11,16) we had spent a mean of 107min., which may be near the open procedures time. Previous adult experience, same team, routine and focusing on simplifying every step certainly play a role in the operative time.…”
Section: Discussionmentioning
confidence: 82%
“…The dismembered LP for treatment of PUJ obstruction in children was first described in 1995 (5). Since then, a few pediatric large se- Conversion to open procedure 0 (8). However, while early series had reported anastomotic stenosis in babies (9,10), subsequent studies demonstrated feasibility irrespective of patient age and weight (6,7,(11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations